Evaluating the Quality of Education at Dentistry School of Tehran University of Medical Sciences - Farzianpour, Fereshteh (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: Educational evaluation is a process which deals with data collection and assessment of academic activities’ progress. In this research, educational evaluation of Dentistry School of Tehran University of Medical Sciences, which trains students in undergraduate and residency courses, was studied. METHODS: This descriptive study was done with a model of educational evaluation in ten steps and 13 fields including purposes and mission objectives, management and organization, academic board members, students, human resources and support, educational, research, health and treatment spaces, educational, diagnostic, research and laboratory tools, educational, research, health and treatment programs and courses, process of teaching and learning, evaluation and assessment, alumni, and patients satisfaction. Data were collected using observation, interviews, questionnaires, and checklists. RESULTS: Results of the study were mainly qualitative and in some cases quantitative, based on defined optimal situation. The total mean of qualitative results of educational evaluation of dentistry school in all 13 fields was 55.98% which is relatively desirable. In the case of quantitative ones, results of some fields such as treatment quality of patients and education and learning of the students were relatively desirable (61.32% and 60.16% respectively). CONCLUSION: According to the results, educational goals and missions, educational and research facilities and spaces which were identified as the weakest areas need to be considered and paid more serious attention.